Pengembangan Pendidikan Komputer Untuk Meningkatkan Kemampuan Digital Siswa - Maknuni, Jauharil (Jurnal Aktual Pendidikan Indonesia, 2024)
Computer education plays an essential role in enhancing students' digital literacy in today's digital era. This study aims to analyze the effectiveness of computer-based learning in improving students' technological skills in secondary schools. The research method used in this study is a literature review, analyzing various previous studies discussing the implementation of computer education in the educational field. The results show that integrating computer education into the school curriculum positively impacts various aspects, such as increasing problem-solving skills, creativity, and the ability to adapt to new technologies. Moreover, computer education contributes to enhancing students' digital literacy and critical thinking skills. In the continuously evolving digital era, students' ability to use productivity software, understand basic programming, and maintain digital security is crucial. Previous studies indicate that students who receive computer education are better prepared to face technological challenges than those who do not. Therefore, innovative and adaptive learning strategies are necessary to ensure that computer education continues to develop in line with technological advancements. Schools need to improve access to technological devices, provide training for teachers, and design curricula that focus more on developing 21st-century skills.